Declining Prevalence of Helicobacter Pylori Infection- A 13C Urea Breath Test (UBT) Based Study in Symptomatic - Ahmed, Mian Mashhud; Saeed, Atia; Ali Masum, Abu Shams Md Hasan; Md Mohiuddin, -; Rahman, Anisur (Anwer Khan Modern Medical College Journal, 2019)
Background: Helicobacter pylori (HP) infection is an important cause of peptic ulcer disease (PUD) in the world. This study was aimed to know the trend of H.P. infection among the symptomatic subjects Method: This was a retrospective observational study conducted from January 2015 to July 2018 in three different hospitals in Dhaka city. Patient who presented with dyspepsia underwent 13C urea breath test. Positive cases were analyzed. Results: A total 1343 patients were taken for UBT where 308 (23%) patients were found positive. The mean age group was 41.21+13.6. Male were more infected (61%) than female (39%). Conclusion: Improving sanitary and hygienic condition of this region along with significantly increasing HP eradication therapy and PPI use by the symptomatic individuals might have contributed to the decreasing trend of infection Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 121-124